2020
DOI: 10.16910/jemr.13.2.13
|View full text |Cite
|
Sign up to set email alerts
|

The role that composition plays in determining how a viewer looks at landscape art

Abstract: Viewing artworks may be subject to the same processes as everyday scene selection in respect of gaze behaviour. However, artists may employ carefully constructed composition in their paintings to lead the eyes of viewers along a predetermined path. This paper investigates whether composition is successful through comparison of expected scanpaths (constructed using the known intention of the artist) and actual scanpaths (as captured using an eye-tracker) based on a loci and sequence similarity index. The findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It is therefore revealing to analyse which fixations are frequently repeated. (Beelders & Bergh, 2020;Sancarlo et al, 2020) have shown that often repeated saccades do correlate with the structure, the "composition" of paintings.…”
Section: Oculometric Parameter Of Art Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore revealing to analyse which fixations are frequently repeated. (Beelders & Bergh, 2020;Sancarlo et al, 2020) have shown that often repeated saccades do correlate with the structure, the "composition" of paintings.…”
Section: Oculometric Parameter Of Art Perceptionmentioning
confidence: 99%
“…In the article “The role that composition plays in determining how a viewer looks at landscape art” Tanya Beelders and Luna Bergh ( 2 ) analyse the scan paths of 65 participants looking at three compositions. Based on a similarity index constructed by using the known intention of the artists, the authors conclude that composition is successful in leading the eye, although the order of fixations varies.…”
Section: What Do We Learn From the Articles In This Issue?mentioning
confidence: 99%